Relationship between Visceral Fat and PAI-1 in Overweight Men and Women before and after Weight Loss - Kockx, M.; Leenen, R.; Seidell, J.; Princen, H. M. G.; Kooistra, T. (Thrombosis and Haemostasis, 1999)
This study was aimed at evaluating the relationship between visceral fat accumulation and plasma plasminogen activator inhibitor-1 (PAI-1) levels in healthy, obese men and women undergoing weight loss therapy. The subjects, 25 men and 25 premenopausal women, aged between 26 and 49 years, with an initial body mass index between 28 and 38 kg/m2, received a controlled diet for 13 weeks providing a 4.2 MJ/day energy deficit. Magnetic resonance imaging was used to measure visceral and subcutaneous abdominal fat. Our results show that before weight loss visceral fat was significantly correlated with PAI-1 in men (r = 0.45; p <0.05), but not in women (r = -0.15; ns). The association between visceral fat and PAI-1 in men remained significant after adjustment for age and total fat mass, and multiple linear regression analysis showed a significant independent contribution of visceral fat to plasma PAI-1 levels. Both visceral fat areas and PAI-1 levels decreased significantly with weight loss in both men and women. Changes in visceral fat area were related to changes in PAI-1 in women (r = -0.43; p = 0.05) but not in men (r = -0.01; ns); however, this association in women disappeared after adjustment for total fat mass. We conclude that there is a relationship between visceral fat and PAI-1 in obese men but not in obese women, and that PAI-1 levels decrease substantially (52%) by weight loss, but this change is not related to changes in visceral fat mass per se.
Keywords: PAI-1; obesity; visceral fat; weight loss